ANALISIS SISTEM INFORMASI DELIVERY BERBASIS WEB MOBILE PADA WARUNG MAKAN SETIA KAWAN PRINGSEWU DALAM UPAYA PENINGKATAN OMSET PENJUALAN - Sudewi Sudewi; Khodijah Khodijah (Jurnal AKTUAL, 2018)
One that supports service quality in a restaurant is the order process. The process of ordering food in a restaurant still uses a manual system, so that sometimes a misunderstanding occurs. Therefore, in this study a web-based website was made on the loyal restaurant of Setia Kawan Pringsewu. The method used in this researcher is SDLC (software development life cycle) which has several stages, namely Planning, Analysis, Design, Trial, Implementation and Processing. Making this mobile-based web application uses MysQL as a database. Based on the results of the implementation it can be concluded that this application is able to provide a fairly easy service and make an order.